2013
DOI: 10.1289/ehp.1205838
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Perfluoroalkyl Acids and Markers of Kidney Function among Children and Adolescents Living near a Chemical Plant

Abstract: Background: Serum levels of perfluorooctanoic acid (PFOA) have been associated with decreased renal function in cross-sectional analyses, but the direction of the association is unclear.Objectives: We examined the association of measured and model-predicted serum PFOA concentrations with estimated glomerular filtration rate (eGFR), a marker of kidney function, in a highly exposed population (median serum PFOA, 28.3 ng/mL).Methods: We measured serum creatinine, PFOA, perfluorooctane sulfonate (PFOS), perfluoron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 39 publications
5
100
0
Order By: Relevance
“…Bijland et al (2011) observed that dietary PFOS increased expression of PFOS genes involved in fatty acid uptake and transport in APOE n 3-Leiden.CETP mice. Watkins et al (2013) found that among four PFAAs (PFOA, PFNA, PFHxS, and PFOS), only PFOS was associated with LINE-1 DNA methylation, which is known to regulate gene expression and may influence serum lipids (Nelson et al, 2011). These hypotheses require substantive mechanistic research associated with hypercholesterolemia in the epidemiology studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bijland et al (2011) observed that dietary PFOS increased expression of PFOS genes involved in fatty acid uptake and transport in APOE n 3-Leiden.CETP mice. Watkins et al (2013) found that among four PFAAs (PFOA, PFNA, PFHxS, and PFOS), only PFOS was associated with LINE-1 DNA methylation, which is known to regulate gene expression and may influence serum lipids (Nelson et al, 2011). These hypotheses require substantive mechanistic research associated with hypercholesterolemia in the epidemiology studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additional data on local sources of exposure could help clarify the relationship between intake and biomarkers. Research in a highly exposed population (Watkins et al, 2013) as well as in the general population (Shankar et al, 2011) suggests that serum PFAS concentrations may be highly sensitive to kidney function; for example, age-related declines in glomerular filtration rates (Glassock and Winearls, 2009) should affect PFAS biomarker trends in longitudinal studies by lengthening PFAS residence times in the body during the course of follow-up. There also may be differences between isomers of the same compound in elimination half-lives (Zhang et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 9,600 children aged 1–18 years, an inter-quartile range increase in PFOA serum concentration was associated with a 0.75 ml/min/1.73 m 2 decrease in estimated GFR. 79 Cross-sectional analyses have found that measured PFOS, PFNA and PFHxS serum levels are associated with a decrease in GFR, but the predicted serum PFOA concentrations at the time of enrolment were not statistically associated with GFR. These data raise the possibility that cross-sectional associations between PFAA and GFR might be a consequence, rather than a cause, of reduced kidney function.…”
Section: Perfluoroalkyl Acidsmentioning
confidence: 99%
“…These data raise the possibility that cross-sectional associations between PFAA and GFR might be a consequence, rather than a cause, of reduced kidney function. 79 A longitudinal study of PFAA exposure among individuals living near a hazardous waste site failed to show an effect on GFR, based on residential address and distance from the waste site. 79 Finally, a study of 1,961 12–19-year-old adolescents included in NHANES 2003–2010 identified that those in the highest quartile for PFOA and PFOS excretion had a 6.6–9.5 ml/min/1.73 m 2 lower estimated GFR than those in the lowest quartile (A. Kataria et al , unpublished work).…”
Section: Perfluoroalkyl Acidsmentioning
confidence: 99%